Predicted grade point average and the actual grade point average of first year high school students of St. Scholastica's College Manila - Alcantara, Alma Consolacion (2014)
The study investigated the relationship between the predicted grade point average (PGPA) and the actual high school grade point average (GPA) of the first year high school students in 3 consecutive school years, 2008-2009, 2009-2010, and 2010-2011. The Predicted Grade Point Average (PGPA) represents the prediction equation model derived from a study in SY 1999-2000 which consists of five cognitive data identified as predictors of academic performance in high school. The five predictors arranged in order of greater contribution were: Science grade school GPA, Math GPA, IQ, English GPA, and scores in Vocabulary achievement (Salubayba, 1999). PGPA is one of the bases for admission in high school for the graduates of the grade school unit. The first year Grade Point Average (GPA) represents the actual performance and the success achieved within the immediate transitional year in high school. The participants are selected according to the availability of their PGPA data, hence, this study limits the subjects to the graduates of the grade school unit of St. Scholastics's College Manila. The data was from the three batches (n=612) were analyzed using Pearson R. The results showed big relationship between the predicted GPA and GPA among students from 2008-2009, 2009-2010 and 2010-2011. As evidenced by these results, this study found out that the prediction equation model (PGPA-SSC Guidance 1999) is reliable and can predict the success of the first year high school students. This may suggest that PGPA may determine the predict and academic readiness and later success of entering high school students and the prediction equation model can still be useful and effective in determining the achievement and performance of prospective first year high school students.
Keywords: Grade Point Average -- First Year High School Students; Academic Performance -- First Year High School Students